The Elevated Expressions of Anti-lipopolysaccharide Factors After Priming Stimulation Confer Lastingly Humoral Protection in Crab Eriocheir sinensis - Wang, Weilin; Li, Yan; Fan, Siqi; Lian, Xingye; Cao, Wanqing; Song, Xiaorui; Yi, Qilin; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2021)
Innate immune memory is a new hotspot in study of immunity, and the memory effects in invertebrates (immune priming) are also accumulating reported in various organisms. Both cellular and humoral immune reactions are speculated to involve in immune priming, leaving the detailed molecular mechanism puzzling and controversial. In Chinese mitten crab Eriocheir sinensis, the increased antibacterial activity and enhanced protection of haemolymph were detected after priming stimulation with Aeromonas hydrophila, but the exact molecular mechanism is still not well understood. In the present study, the protective effect of primed haemolymph was further validated by the increased survival rate of naïve crabs receiving a transfusion of primed haemolymph. By proteomic analysis, there were 474 proteins identified from the primed haemolymph, which were mostly functionally annotated in transport and metabolism classes. A total of 70 proteins were found to be differentially expressed in haemolymph at 12 h and 7 day after A. hydrophila priming stimulation, and among them, anti-lipopolysaccharide factor 1 (EsALF-1) and 3 (EsALF-3) were screened out with significantly (p < 0.05) up-regulated expression. EsALF-1 and EsALF-3 were highly expressed in haemocytes compared with other tissues, and their increased expressions were validated at both mRNA (in haemocytes) and protein (in haemolymph) level after the second challenge of A. hydrophila. In naïve crabs receiving injection with recombinant protein of EsALF-1 (rEsALF-1) or EsALF-3 (rEsALF-3), their survival rate was significantly (P < 0.05) increased upon A. hydrophila challenging. By contrast, the survival rate of the primed crabs was significantly reduced after EsALF-1 or EsALF-3 ablation by injection with their antibody, respectively. Furthermore, the expressions of elements in EsTLR1-EsMyd88–EsPelle-EsALF pathway were all increased (p < 0.05) after A. hydrophila priming stimulation, while decreased (p < 0.05) after EsTLR1 was knocked down by RNAi. In addition, the enhanced expressions of EsALF-1 and EsALF-3 after A. hydrophila priming could sustain for four weeks. All the results suggested that EsTLR1-mediated productions of EsALF-1 and EsALF-3 in haemolymph, played indispensable role in A. hydrophila induced month-long humoral protection, which provide solid evidence for humoral immune priming effects in crabs and valuable reference for understanding immune memory in invertebrates.